Effect of intravenous iron supply in patients with heart failure with reduced ejection fraction – a literature review - Dąbek, Katarzyna; Ochwat, Michał; Sudoł, Maria; Piekarska, Martyna; Mierzwa, Gabriela; Kajtel, Aleksandra; Skowronek, Anna (Quality in Sport, 2024)
Introduction and Purpose Iron deficiency in patients with heart failure is a common problem of which they are often unaware. It is associated with a worse prognosis compared to patients suffering with heart failure without iron deficiency. An important point in the diagnosis in patients with heart failure would be the determination of iron in the blood, in order to catch patients eligible for intravenous iron administration. The aim of the study was to investigate whether intravenous iron administration could affect quality of life in these patients and further reduce hospital admissions for heart failure exacerbations and deaths caused by cardiovascular events. Material and Methods A comprehensive literature review was conducted using the PubMed and Google Scholar database. We used the key words: ‘heart failure’ in combination with medical terms referring to iron status or its therapeutic use , “iron deficiency”, “intravenous iron”, “intravenous ferric carboxymaltose”, “intravenous ferric derisomaltose” in various combinations. Results and conclusions Intravenous iron administration in patient with heart failure with reduced ejection fraction and iron deficiency reduces symptoms, improves quality of life, exercise tolerance and reduces hospital admissions for heart failure. It is very important to actively look for iron deficiency in patients with heart failure, and then patients who meet the criteria should be provided with an intravenous iron administration.